1994
DOI: 10.1017/s0266462300006632
|View full text |Cite
|
Sign up to set email alerts
|

The Introduction and Evaluation of MRI in Japan

Abstract: Not only is the number of computed tomography (CT) units relative to population in Japan the highest in the world, that of magnetic resonance imaging (MRI) units is second only to the United States. This study examines the diffusion pattern of MRI in Japan, as well as the factors that influence it. The number of MRI units has increased sharply, closely following CT, as has been the case in the United States. This pattern of diffusion in Japan was determined mainly by the following factors: the technological at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
10

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 21 publications
1
16
0
10
Order By: Relevance
“…Although appraisal and information relating to the appropriate utilisation and financial operation of MR units are indispensable, such data are often lacking [2]. In the USA and Europe, high technology medicine is seen as the primary cause of increased health care costs, the result being that cost control cannot be achieved without limiting its usage [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although appraisal and information relating to the appropriate utilisation and financial operation of MR units are indispensable, such data are often lacking [2]. In the USA and Europe, high technology medicine is seen as the primary cause of increased health care costs, the result being that cost control cannot be achieved without limiting its usage [3].…”
Section: Introductionmentioning
confidence: 99%
“…Because the medical device industry in Japan expands a market by developing simpler and cheaper models as well as discounting prices, the medical device market is highly competitive [3,19]. In this study, a drastic decrease in the purchase price of each type of MR unit was observed, especially in the superconducting (0.5-T) and permanent (0.2-T) units made by Japanese manufacturers (Table 5).…”
Section: Discussionmentioning
confidence: 74%
“…Despite the greater cost of units with superconducting magnets, large hospitals and university hospitals, which have greater resources, in Japan acquire these units to maintain their prestige and competitive positions and to attract patients and physicians, taking a global managerial point of view rather than one of short-term profitability [3,22]. Comparisons between Japan and the United States must be made cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…In some areas of health care the fee-for-service system and the suppression of reimbursement prices motivates the providers to increase their volume of service, possibly to a level where the marginal benefit falls below zero. This is particularly evident in pharmaceuticals and diagnostic procedures (Hisashige, 1994;Oliver et al, 1999).…”
Section: Providersmentioning
confidence: 99%